2019
DOI: 10.3390/jcm8122229
|View full text |Cite
|
Sign up to set email alerts
|

Trials of a Fluorescent Endoscopic Video System for Diagnosis and Treatment of the Head and Neck Cancer

Abstract: This article presents the results of intraoperative fluorescent diagnostics via the endoscopic system for assessing the quality of photodynamic therapy (PDT) of head and neck cancer. The diagnosis and PDT procedures were performed on the five patients with malignant neoplasms of the vocal cords, lateral surface of the tongue, and trachea and cancer of the left parotid salivary gland. Molecular form of chlorin E6 (Ce6) was intravenously administered with a 1.0–1.1 mg/kg concentration for PDT. Fluorescent diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The Ce6 antitumor effect also includes damage to both pathological cells by the mechanism of necrosis and/or apoptosis, and tumor-associated macrophages [34,35]. The use of Ce6 during FD and PDT, according to the latest published data, shows high diagnostic and therapeutic efficacy [36][37][38][39][40][41]. Moreover, Ce6 demonstrates higher therapeutic efficacy and fewer side effects compared to hematoporphyrin-based PS [42] Normalization of the fluorescence index was performed by assigning the fluorescence index value of 10 to the DM lining, which allowed to intraoperatively identify areas with increased fluorescence intensity of Ce6 in all three patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ce6 antitumor effect also includes damage to both pathological cells by the mechanism of necrosis and/or apoptosis, and tumor-associated macrophages [34,35]. The use of Ce6 during FD and PDT, according to the latest published data, shows high diagnostic and therapeutic efficacy [36][37][38][39][40][41]. Moreover, Ce6 demonstrates higher therapeutic efficacy and fewer side effects compared to hematoporphyrin-based PS [42] Normalization of the fluorescence index was performed by assigning the fluorescence index value of 10 to the DM lining, which allowed to intraoperatively identify areas with increased fluorescence intensity of Ce6 in all three patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Ce6 antitumor effect also includes damage to both pathological cells by the mechanism of necrosis and/or apoptosis, and tumor-associated macrophages [ 34 , 35 ]. The use of Ce6 during FD and PDT, according to the latest published data, shows high diagnostic and therapeutic efficacy [ 36 , 37 , 38 , 39 , 40 , 41 ]. Moreover, Ce6 demonstrates higher therapeutic efficacy and fewer side effects compared to hematoporphyrin-based PS [ 42 ]…”
Section: Discussionmentioning
confidence: 99%
“…Adverse reactions in patients including skin solar sensitivity, pain in the irradiation area, and vocal cord edema and adhesion were reported 223 , 224 . Some studies have shown that sensitizers can also be used for clinical diagnosis and treatment 225 , 226 . PDT is usually used in combination with other therapies in clinic.…”
Section: Clinical Application Against Cancermentioning
confidence: 99%
“…The results of studies [ 23 , 24 ] have demonstrated the high efficiency of PDT with chlorin e6 (Ce6) for the treatment of cervical neoplasms. Ce6 is a promising PS with significant diagnostic and therapeutic efficacy [ 25 , 26 , 27 , 28 ]. Ce6 is a second-generation PS with high efficiency and minimal dark phototoxicity [ 29 ].…”
Section: Introductionmentioning
confidence: 99%